Question
upstudy study bank question image url

What are the two solutions of \( 2 x^{2}=-x^{2}-5 x-1 \) ? the \( y \)-coordinates of the intersection points of the graphs of \( y=2 x^{2} \) and \( y=-x^{2}-5 x-1 \) the \( x \)-coordinates of the intersection points of the graphs of \( y=2 x^{2} \) and \( y=-x^{2}-5 x-1 \) and

Ask by Sherman French. in the United States
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are \( x = -\frac{5 + \sqrt{13}}{6} \) and \( x = -\frac{5 - \sqrt{13}}{6} \). The corresponding \( y \)-coordinates are \( y = \frac{19 + 5\sqrt{13}}{18} \) and \( y = \frac{19 - 5\sqrt{13}}{18} \).

Solution

Solve the quadratic equation by following steps: - step0: Solve using the quadratic formula: \(2x^{2}=-x^{2}-5x-1\) - step1: Move the expression to the left side: \(3x^{2}+5x+1=0\) - step2: Solve using the quadratic formula: \(x=\frac{-5\pm \sqrt{5^{2}-4\times 3}}{2\times 3}\) - step3: Simplify the expression: \(x=\frac{-5\pm \sqrt{5^{2}-4\times 3}}{6}\) - step4: Simplify the expression: \(x=\frac{-5\pm \sqrt{13}}{6}\) - step5: Separate into possible cases: \(\begin{align}&x=\frac{-5+\sqrt{13}}{6}\\&x=\frac{-5-\sqrt{13}}{6}\end{align}\) - step6: Rewrite the fraction: \(\begin{align}&x=\frac{-5+\sqrt{13}}{6}\\&x=-\frac{5+\sqrt{13}}{6}\end{align}\) - step7: Rewrite: \(x_{1}=-\frac{5+\sqrt{13}}{6},x_{2}=\frac{-5+\sqrt{13}}{6}\) To find the solutions of the equation \( 2x^{2} = -x^{2} - 5x - 1 \), we first rearrange it into standard form: \[ 2x^{2} + x^{2} + 5x + 1 = 0 \] This simplifies to: \[ 3x^{2} + 5x + 1 = 0 \] Now, we can solve this quadratic equation. The solutions are: \[ x_{1} = -\frac{5 + \sqrt{13}}{6}, \quad x_{2} = -\frac{5 - \sqrt{13}}{6} \] ### \( y \)-coordinates of the intersection points To find the \( y \)-coordinates of the intersection points, we substitute the \( x \)-coordinates back into either of the original equations. We'll use \( y = 2x^{2} \). 1. For \( x_{1} = -\frac{5 + \sqrt{13}}{6} \): \[ y_{1} = 2\left(-\frac{5 + \sqrt{13}}{6}\right)^{2} \] 2. For \( x_{2} = -\frac{5 - \sqrt{13}}{6} \): \[ y_{2} = 2\left(-\frac{5 - \sqrt{13}}{6}\right)^{2} \] Now, let's calculate these \( y \)-coordinates. ### Calculating \( y_{1} \) and \( y_{2} \) 1. For \( y_{1} \): \[ y_{1} = 2\left(-\frac{5 + \sqrt{13}}{6}\right)^{2} = 2 \cdot \frac{(5 + \sqrt{13})^{2}}{36} = \frac{2(25 + 10\sqrt{13} + 13)}{36} = \frac{2(38 + 10\sqrt{13})}{36} = \frac{19 + 5\sqrt{13}}{18} \] 2. For \( y_{2} \): \[ y_{2} = 2\left(-\frac{5 - \sqrt{13}}{6}\right)^{2} = 2 \cdot \frac{(5 - \sqrt{13})^{2}}{36} = \frac{2(25 - 10\sqrt{13} + 13)}{36} = \frac{2(38 - 10\sqrt{13})}{36} = \frac{19 - 5\sqrt{13}}{18} \] ### Summary of Results - The \( x \)-coordinates of the intersection points are: - \( x_{1} = -\frac{5 + \sqrt{13}}{6} \) - \( x_{2} = -\frac{5 - \sqrt{13}}{6} \) - The \( y \)-coordinates of the intersection points are: - \( y_{1} = \frac{19 + 5\sqrt{13}}{18} \) - \( y_{2} = \frac{19 - 5\sqrt{13}}{18} \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy